Elementos para uma Teoria Enunciativa da Educação Popular - Alcantara, Marcos Angelus Miranda de (2017)
The problem of Popular Education Research is inserted without debate on the epistemological ruptures of Modernity. It is also correlated to recent events in the history of Brazilian education: National Institute of Educational Studies and Researches (INEP) creation in 1937; in the institutionalization of the Brazilian Post-Graduation in 1965; and the creation of National Association of Post-Graduation and Research in Education (ANPED) in 1978. Specifically, the object of this study is delimited to the contribution of the Archaeological Discourse Analysis to the research field of Popular Education in Brazil. From it elapsed the formulation of the thesis that the Archaeological Discourse Analysis may contribute with elements to an Enunciative Theory of Popular Education. From the theoretical/methodological point of view, the investigation appropriates the archaeological contributions of Michel Foucault (2007; 2008; 2010). From Saussure (2006), Peirce (2008) and Frege (2010), we use the notion of sign, treating it, however, as a constitutive element of the utterance when considering the rupture of its trichotomic constitution. It uses methodological procedures of mapping, excavation of the speech area and analysis and description of utterances, according to Alcantara and Carlos (2013). In the debate of the thesis, the text first runs through an order of present discourse in the debate about the refoundation of Popular Education for the century XXI, in dialogue with Beisiegel (1984), Freire (1987), Brandão (2006), Guevara (2006), Streck (2012), Carrillo (2013), among others. After explaining this discussion, it enters the academic production in the theses and dissertations in Popular Education in some programs distributed over the country, mapping its themes, its problems, its objects and its theoretical/methodological approaches. From the epistemological point of view, the survey analyzes the approaches that underlie such research, such as trends in Marxism, documentary methods, biographical methods and language. Two investigative trends are identified: the referential and the meaningful. In the universe of studies of the language field, the research accesses the production of the Group of Studies and Researches in Youth and Adults Education from the Post-Graduation Program in Education of the Paraíba Federal University (GEPEJA/PPGE/UFPB), focused on Foucaultian archeology that allows the emergence of specific objects of study, only possible through an archaeological parameter for the problems: objects in the utterance field, on general rules and laws of functioning of discourses on Youth and Adults Education (EJA), on Popular Education in Health and on Education and Visuality, among others. These are surveys that deal with the enunciative dimension of Popular Education. In this perspective, they are identified as conditions of possibility of existence of the Popular Education enunciation, initially in the excavation of its enunciative signs, then by means of an analysis and description of its domain fields: anthropophilosophical, cognitive-epistemic, ideopolitical, generic-abstract, socio-historical and organizative-operationative. I concluded that from a series of rules, positions of subjects, enunciative functions and correlates, these domains establish a series of possibilities of speaking, writing and articulating discourses on education, being Popular Education a possibility that triggers a series of enunciative signs of democracy, of citizenship, of participation, of human rights, etc. Therefore, these domains identified and described constitute elements for an Enunciative Theory of Popular Education.